Implementasi Manajemen Kurikulum di Madrasah Aliyah Negeri - Rahmi Nurul Najma; Andi Mappincara; Irmawati Irmawati (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
The purpose of this study is to find out how the implementation of curriculum management in Madrasah Aliyah Negeri. This research approach is qualitative with a case study type of research. This research was conducted in MAN 2 Makassar City, the data sources in this study were curriculum wakamad, student wakamad, two teachers, and one student. Data collection techniques use observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusions. Data checking and validation using data trianggulation techniques. The results of the research obtained are 1) At the planning stage of implementing the learning curriculum, namely the 2013 curriculum and class X responding to the independent curriculum, also before the new school year, a working meeting was held which was divided into 5 commissions to discuss work programs. The subject teacher makes a lesson plan that has been approved by the principal before it is implemented. 2) At the implementation stage of Madrasah Aliyah Negeri 2 Makassar City has a club and extracurricular as a forum for students to learn. Teachers enter the MGPM organization by involving teachers to compile lesson plans, prepare facilities and infrastructure for the learning process, and arrange a comfortable and pleasant learning environment. 3) At the evaluation stage, it is carried out routinely and not routinely. Evaluation of the work program is carried out in accordance with the implementation of the program and when there is a discussion that will be discussed further, a meeting will be held. For student assessment, an assessment of students' daily lives is carried out, both daily tests, practices, midterm tests, end-of-semester tests and student personality scores which are then accumulated. After that, it will be discussed at the class upgrade determination meeting. The credit system is also applied, namely students can graduate quickly with a study period of 2 years and no later than 4 years.